Performance analysis of the Indian pharmaceutical industry : a global outlook - Chakraborty, Chandrima; Pal, Dipyaman (Emerald Publishing Limited, 2025)
The Indian Pharmaceutical Industry (IPI) has grown exponentially over the last few decades; however, recent global competition is forcing the industry to examine its performance focusing on productivity, efficiency and growth capabilities. While the industry as a whole has proved resilient to economic slowdowns, the performance of individual firms in the industry have displayed large disparities. There is also evidence of disparity among the Indian states. Efficiency and productivity act as good performance indicators. Performance Analysis of the Indian Pharmaceutical Industry estimates the extent of technical efficiency (TE) and total factor productivity growth (TFPG) of IPI and to identify their major affecting factors. A comparison between efficiency and TFPG of IPI is made, looking at the common factors responsible for variations in efficiency and TFPG of IPI. Chakraborty and Pal examine the import and export of Indian medicines to understand the place of the industry on a global scale and assess what can be done to become more competitive. The international comparison of this study will appeal and be useful for researchers, industry professionals and policy makers.